Hubungan Pemberian Asi Eksklusif Dengan Perkembangan Motorik Kasar Bayi Umur 7-12 Bulan Di Wilayah Kerja Puskesmas Tanjung Karang Kota Mataram - Baiqtinda Partipasari; Abdul Salam (Poltekkes Kemenkes Mataram, 2017)
Background. Based on data Riskesdas 2013 showed that the percentage of breast-feeding only in the last 24 hours decreased with increasing age of the baby with the lowest percentage of children aged 6 months (30.2%). The data show in Mataram city only (65.96%) of all mothers breastfeeding Exclusive breastfeeding apply. Coverage of exclusive breastfeeding in the Puskesmas Tanjung Karang in 2012, exclusive breastfeeding in the working area of the health center Tanjung karang (59.40%) is still below the target of 80% and the expectation is ranked third highest of ten health centers in the region Mataram city. Research Methods. Based on the type, this study is an observational analytic studies and in terms of the time these are cross-sectional study in which all variables were collected in same time. Gross motor development of infants aged 7-12 months were collected first, then ask for a history of exclusive breastfeeding at age 0-6 months. Research Result. From 85 samples based on those age, the average age most babies are 9 months old is as much as 24.8%. Based on those sex most (56.5%) male sex. Exclusive breastfeeding bulk of the sample (64.7%) received exclusive breastfeeding and the development of gross motor bulk of the sample (70.6%) in the normal category. Based on statistical tests showed no significant relationship p = 0.558 for the higher value of α = 0.05, meaning that there is no relationship between the Exclusive Breastfeeding Babies With gross motor development Age 7-12 Months On The area of health center Tanjung Karang, Mataram City. Conclusion. exclusive breastfeeding has no relationship with gross motor development because apart from exclusive breastfeeding motor development can be caused by several things including the lack of stimulation can also cause irregularities grow and develop even disorders that are settled.